MENCERMATI NILAI KEARIFAN LOKAL PADA MASYAKAT PETANI DI DESA KAMELANTA KABUPATEN BUTON - La Parasit (Jurnal Ilmiah Sosiologi Agama (JISA), 2025)
The agricultural sector plays a central role as the backbone of Indonesia's economy, where its role is very important in ensuring food security, creating employment opportunities, and providing income for the population, especially in rural areas. This study aims to examine and document the values of local wisdom that are still alive and practiced by the farming community in Kamelanta Village, Buton Regency, particularly in the context of agricultural land clearing activities. The research approach used is qualitative, with a descriptive analysis model that aims to further explain the phenomena occurring in the field, where qualitative data is obtained from direct observation and research in the field. Data collection is divided into two types: primary data and secondary data. Primary data includes interviews and observations. The results of this study found that the local wisdom of the Kamelanta Village community in Buton Regency, especially in the activity of clearing agricultural land in the area, has positive values for community life, namely (1) Religious values regarding belief in God Almighty, (2) Values of togetherness and mutual cooperation in clearing new agricultural land, (3) Furthermore, holding deliberations to reach consensus before deciding on matters for the benefit of the community. The values of local wisdom held by the Kamelanta Village community foster harmony among the community